2001
DOI: 10.1063/1.1415463
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved photoionization: Influence of the 4σ→kσ shape resonance on CO+(B 2Σ+) rotational distributions

Abstract: We present experimental and theoretical results on rotational distributions of CO ϩ (B 2 ⌺ ϩ ) photoions. Rotational distributions were determined for both the v ϩ ϭ0 and v ϩ ϭ1 vibrational levels following photoionization of cold (T 0 Ϸ9 K) neutral CO target molecules. Data were generated using dispersed ionic fluorescence over a wide range of photoelectron kinetic energies, 0рE k р120 eV, which allows one to interrogate the ionization dynamics. This wide spectral coverage permits illustrative comparisons wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…This prediction is also confirmed by angle-resolved photoionization experiments on H 2 molecules [52]. The orbital approximation outlined here is not suitable to describe the energy dependence of the photoionization dynamics and fails to describe the effects of shape resonances and Cooper minima on the rotational structure of photoelectron spectra [53][54][55][56][57]. It does, however, provide a useful framework to discuss rotational intensities in photoelectron spectra: it assists in the assignment of vibronic symmetries, it enables one to detect anomalies in the photoionization dynamics and it helps to reveal vibronic interactions in the molecular cations.…”
Section: Introductionsupporting
confidence: 62%
“…This prediction is also confirmed by angle-resolved photoionization experiments on H 2 molecules [52]. The orbital approximation outlined here is not suitable to describe the energy dependence of the photoionization dynamics and fails to describe the effects of shape resonances and Cooper minima on the rotational structure of photoelectron spectra [53][54][55][56][57]. It does, however, provide a useful framework to discuss rotational intensities in photoelectron spectra: it assists in the assignment of vibronic symmetries, it enables one to detect anomalies in the photoionization dynamics and it helps to reveal vibronic interactions in the molecular cations.…”
Section: Introductionsupporting
confidence: 62%
“…2,4 The higher energy regime is featureless because there is no shape resonance at higher energies, and the Cooper minima are relatively weak. 30 For N 2 , the vibrational branching ratios vary from 100 to 200 eV, while at the lower energy the results are comparatively constant. The high energy behavior results from the strong dependence of the Cooper minima on bond length.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the rotational distributions for CO were relatively flat in the lower energy region 1,2,30 ͑i.e., 20рh р50 eV) while the vibrational distributions vary significantly in this same region. Similarly, polarization data for CO 3,4 in the high energy region demonstrated that the photoelectron is ejected preferentially along the molecular axis, while the vibrational and rotational data were insensitive to this aspect of the photoelectron ejection.…”
Section: Resultsmentioning
confidence: 99%